4. THE NUTRITIONAL STATUS OF PATIENTS WITH BETA THALASSEMIA MAJOR: A SCOPING REVIEW (Vietnam Journal of Community Medicine, 2024)
Objective: This study aimed to review and summarize the existing evidence on the nutritional status of patients with beta thalassemia major.Methods: A scoping review was conducted using the Medline database via PubMed. Seven studies from six countries, involving 836 participants, met the inclusion criteria. Data were extracted on anthropometric measurements, body composition, laboratory indicators, and dietary intake.Results: The findings indicated a high prevalence of malnutrition, particularly among children with beta thalassemia major. Anthropometric data showed significantly lower weight, height, and body mass index compared to healthy individuals. Body composition analysis revealed lower fat percentages and higher muscle mass in children, while adults exhibited decreased lean mass and increased fat mass, with 64.2% classified as obese with sarcopenia. Laboratory results showed deficiencies in serum vitamin D and cholesterol, though calcium and phosphorus levels remained normal. Dietary intake assessments revealed inadequate energy and nutrient intake, particularly for macronutrients and key micronutrients such as calcium, phosphorus, and zinc.Conclusion: Patients with beta-thalassemia major are at high risk of malnutrition, which is associated with both disease and treatment factors. Routine nutritional assessments and tailored interventions are critical for improving the nutritional status and overall health outcomes of this vulnerable population.
Keywords: nutritional status; patient; beta thalassemia major; scoping review; malnutrition